Occupational Safety Health and Work Motivation on Worker Performance Construction Projects - Sunarjo, Daniel Kurniawan; Amin, Mawardi (Universitas Ibn Khaldun Bogor, 2025)
Many construction companies still employ their workers without caring about the implementation of accident risks, by paying attention to work safety, it is expected that the performance of the workers will increase. This study aims to analyze the influence of occupational safety and health factors and worker motivation factors that affect the performance of workers in residential construction projects. The relationship between occupational safety and health, worker motivation and worker performance will be made in a path diagram model, and analyzed using SEM-PLS with a sample of 72 respondents. The results of the study found that the dominant factors in occupational safety and health are worker health monitoring, emergencies, personnel selection and placement, and hazard inspections. Meanwhile, the dominant factors that influence the motivation of craftsmen are wages, timely payment, and continuity (job security). In residential construction projects, occupational safety and health have a significant positive effect (P <0.0.5) on the motivation of craftsmen, in addition, worker motivation also has a significant positive effect on worker performance. In addition, occupational safety and health also have a significant positive effect directly on worker performance.